Perlindungan Hukum Pelaku Tindak Pidana Aborsi Korban Pemerkosaan - Nuri Yani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The right to life is one of the human rights stated in the constitution of the Republic of Indonesia. In Indonesia, abortion is generally prohibited by law. However, for rape victims, abortion is considered an option that needs to be considered to protect the victim. However, until now there is still legal uncertainty regarding the gestational age limit for abortion for rape victims. The problem formulated is how the law protects victims and the implications of regulatory inequality. Using a normative legal approach, the theoretical study examines human rights, reproductive health, and feminism, which emphasizes the victim's right to choose abortion to reduce suffering. The results of the discussion show the unclear rules on gestational age in the Health Law and PP No. 28 of 2024, which differs from the 14-week limit in the Criminal Code. In conclusion, harmonization of regulations is needed to provide legal certainty for victims and medical personnel in carrying out abortions.